New, highly versatile bimolecular photoinitiating systems for free-radical, cationic and thiol–ene photopolymerization processes under low light intensity UV and visible LEDs for 3D printing application. Issue 13 (19th February 2020) - Hola, Emilia; Topa, Monika; Chachaj-Brekiesz, Anna; Pilch, Maciej; Fiedor, Paweł; Galek, Mariusz; Ortyl, Joanna
Abstract : 1-Amino-4-methyl-naphthalene-2-carbonitrile derivatives are proposed for the role of photosensitizers of iodonium salt during the photopolymerization processes upon near UV-A and visible ranges. Abstract : 1-Amino-4-methyl-naphthalene-2-carbonitrile derivatives are proposed for the role of photosensitizers of iodonium salt during the photopolymerization processes upon near UV-A and visible ranges. Remarkably, 1-amino-4-methyl-naphthalene-2-carbonitrile derivatives are highly versatile allowing access to photoinitiating systems for (i) the cationic photopolymerization of epoxide monomers with a ring opening mechanism and vinyl ether monomers with chain growth mechanisms (ii) the free-radical photopolymerization of acrylate monomers, (iii) the photopolymerization of interpenetrated polymer networks (IPNs) based on epoxide and acrylate monomers under air and under laminate in an oxygen-free atmosphere (iv) the thiol–ene photopolymerization processes. Excellent polymerization profiles are obtained during all types of photopolymerization processes. The initiation mechanisms are analyzed through steady state photolysis, cyclic voltammetry and fluorescence experiments. Moreover, the newly developed bimolecular photoinitiating systems were investigated by applying an additive manufacturing process under visible light sources. Furthermore, vat photopolymerization processes using IPN compositions, which are polymerizable by using new photoinitiating systems, provide high resolution and speeds. For these reasons, new bimolecular photoinitiating systems are promising initiators for photopolymerization-based 3D printing process to fabricate 3D structures.